Farm Demonstration of Influence of Cattle Manure Rates on the Agronomic Parameters of Three Okra (Abelmoschus esculentus) Varieties for Small Scale Farmers in Wukari, Taraba State, Nigeria (UNIZIK Journal of Agricultural Economics and Extension, 2025)
Field experiments to investigate the influence of Cattle manure on Okra (Abelmoschus esculentus) Varieties was carried out at the Teaching and Research Farm of the Faculty of Agriculture and Life Sciences of Federal University Wukari, Taraba State during the 2024 growing season. Treatment consists; 0t/ha,10t/ha, 15t/ha and 20t/ha rates of cattle manure and varieties were Clemson, prerana Fi and local variety and laid out in a split plot design with three replications. Data were collected on growth and yield parameters (Plant height, number of leaves per plant, and fresh pod weight). Results obtained indicated that growth and yield of okra was lowest in control treatments which showed that the cattle manure used in the study positively influenced the performance and yield of okra. Cattle manure positively increased okra plant height and number of leaves compared to control treatments. There was significant effect with in respect to number of leaves in 2024 growing season. Stem girth was significantly increased with cattle manure compared to control treatments. According to this research the experiments it could be deduced that 20t/ha cattle manure and prerana Fi   seems to promote higher growth and yield of okra. Thus, it should be recommended for farmers growing okra in this zone.